Infective Endocarditis in the Colombian Caribbean Region: Clinical Profile, Microbiological Insights, and Risk Factors for Mortality - Solarte Bastidas, Gabriela; Herrera Calle, Pedro; Domínguez-Vargas, Alex; Iglesias Pertuz, Shirley; González-Torres, Henry J (Gaceta Médica de Caracas, 2023)
Background: Infective endocarditis (IE) is defined as the infectious and inflammatory process of the heart’s internal structures. It can be caused by a broad group of bacteria and, rarely, fungi, with potentially life-threatening consequences. Objective: To profile bacterial resistance and identify mortality risk factors in IE patients. Methods: This cross-sectional study included clinically diagnosed IE patients. Sociodemographic, comorbidity, clinical, and microbiological data were recorded. Descriptive analyses, Chi-Square/Fisher’s exact tests, and Student’s t-tests examined variables in relation to IE outcomes (survival vs. mortality). Multivariate logistic regression calculated odds ratios and confidence intervals.